Progress of research on privacy protection for data publication and data mining - Jiao WANG; Ke-feng FAN; Yong WANG (网络与信息安全学报, 2016)
With the rapid development of the computer technology, there are more and more data in the society. In order to acquire knowledge from the large amounts of data, collecting and data mining is necessary. However, the privacy information will inevitably be disclosed during the process. So it is particularly important to improve the security of data and protect the useful data to avoid being disclosed. Several methods of data privacy preserving technology were analyzed when data was processed and briefly discussed the international standards which were made by JTC1 about privacy protection. According to its different application fields, the possible future research di-rections was proposed. Certain reference foundation could be provided for people who were in the field of informa-tion security.